TOO MANY OR TOO FEW NORMS: “NORMAL ANOMIE” AS A NEW DEFINITION OF THE PRESENT TIMES - I. V. Katernyi (Vestnik MGIMO-Universiteta)
Book under review: “Normal’naya Anomiya” v Rossii i Sovremennom Mire [Normal Anomie In Russia And Modern World]. Ed. S.A. Kravchenko. Moscow: MGIMO-University, 2017. (In Russian). 281 p.The reviewed publication features a new comprehensive approach to grasp current complexities of the modern society by developing the conception of normal anomie. Authors contribute to reveal the nature of normal anomie as a dispersion of norms and values which entails a permanent reproduction and proliferation of risks and uncertainties in all spheres of human activity. In the provided review, normal anomie is addressed in reference to its common and distinctive features compared with classical sociological conceptions of societal and normative disorganization found in the works o such preeminent scholars as E. Durkheim, R.K. Merton, G. Bataille et al.